2019
DOI: 10.1017/s0007114519000904
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effect of ruminal undegradable protein level and rumen-protected conjugated linoleic acid (CLA) inclusion in the diet of growing goat kids on meat CLA content and quality traits

Abstract: The aim of the present study was to determine the effects of dietary rumen undegradable protein (RUP) level and rumen-protected conjugated linoleic acid (rpCLA) on meat fatty acid (FA) profile, chemical compositions and colour parameters of growing kids. Thirty-two Kurdish goat kids (13·06 ± 1·08 kg body weight) were fed diets differing in RUP level (low = 250 v. high = 350 g/kg of dietary crude protein) supplemented either with 15 g/kg of rpCLA or 12 g/kg of hydrogenated soyabean oil (HSO) for 80 d. Interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Some studies about diet nutrition with meat quality were conducted in sheep [36][37][38][39][40][41][42][43][44][45]. Protes et al (2018) reported the decreased shear force of samples from lambs fed with soybean silage compared to sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies about diet nutrition with meat quality were conducted in sheep [36][37][38][39][40][41][42][43][44][45]. Protes et al (2018) reported the decreased shear force of samples from lambs fed with soybean silage compared to sorghum.…”
Section: Discussionmentioning
confidence: 99%
“…The μ-calpain mRNA expression levels have been upregulated with increasing energy levels in the diet of goats, in contrast to the CAST mRNA expression levels [ 97 ]. Supplementation of diets with rumen undegradable protein and CLAs has decreased total fat content and increased cis-9, and trans-11 CLAs in the intramuscular fat of Kurdish goat kids [ 100 ].…”
Section: Nutritional Effects On the Meat Of Sheep Goats And Cattlementioning
confidence: 99%
“…Protein can be categorised as degradable (RDP) or non-degradable (RUP) depending on its passage through the rumen and its susceptibility to the proteolytic actions of ruminal microbes [ 100 ]. Good sources of degradable protein for cattle include quality pasture, silage, and grazing forages.…”
Section: Nutritional Effects On the Meat Of Sheep Goats And Cattlementioning
confidence: 99%
“…With regard to improving ruminant production, numerous studies have reported that supplementary amino acids or fatty acids could improve production for yaks, sheep, and goats [3][4][5]. Fat usage has become a common strategy for providing energy in animal production.…”
Section: Introductionmentioning
confidence: 99%